GIS A Computing Perspective Third Edition - Duckham, Matt; Sun, Qian (Chayn); Worboys, Michael F. (Taylor & Francis, 2024)
The third edition of GIS has been revised with extensive new content reflecting the significant progress that has been made in the realm of GIS within the last 20 years. Among the new topics covered are graph databases and graph query languages, ontology engineering and qualitative spatial reasoning, geosensor networks and GeoAI.